Zika Virus Infection and a Missed Opportunity - Viroj Wiwanitkit (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2016)
Zika virus infection becomes the big consideration in medicine at pesent since the infection can seriously affect the health of the infected person. Theall et al., noted that "it presents an unprecedented  opportunity to shift public health policy, legislation, and programming to bolster and support the rights of all women to achieve the highest attainable standard of health and well-being now and for the future [1]. Indeed, the problem of Zika virus infection is the present big concern for women around the world. There are many proposed infection control method and most directly involve the women. The role of the clinical microbiology for diagnosis of the disease is confirmed but the issue adding to the post diagnosis phase should be discussed. Since the diagnosis of infection can be the marker of "serious disease" to a person, there must be the good management. This situation is similar to the post HIV diagnosis in the early phase of worldwide HIV epidemic.